Legal Profession Ethics in India - Azad, S A K; Das, Sidhartha (International Journal of Psychosocial Rehabilitation, 2025)
Ethics are principles and values, which together with rules of conduct and laws, standardise a profession, such as the legal profession. They act as a significant guide to confirm right and proper behaviour in the daily practise of the law. If lawyers do not follow to, and promote, principles of justice, fairness and equity, the law itself is brought into disrepute and public confidence in the law will be undermined, thereby hindering access to justice. In order to achieve accountability, it is also important to ensure that rules of ethics, once developed, are publicised amongst the legal profession and the public. To ensure that ethics are enforceable, the legal profession should also put in place effective disciplinary procedures. In India to maintain the honour of legal profession, the Advocate Act 1961 has been passed and established Bar Councils. Under section 49 (1) (c) of Advocates Act breach of Advocates duties codified in regard to the Professional and other misconduct. So a lawyer should be clear in expressing his views and should understand that it is not enough for him alone to understand that his client is right but to prove it to the judge and to the others concerned with the case